Potential of Using New Indole- and Benzimidazo[1,2-C]quinazolines in Anticancer Therapy Based on Mesenchymal Stem Cells - Radzikowska-Bűchner E; Radej S; Niezabitowska E; Sitarz R; Szewc M (Cancer Management and Research)
Elżbieta Radzikowska-Bűchner,1,2 Sebastian Radej,1 Ewa Niezabitowska,3 Robert Sitarz,4,5,* Monika Szewc5,* 1Institute of Medical Sciences, The John Paul II Catholic University of Lublin, Lublin, Poland; 2Radzikowska Clinic, Warszawa, Poland; 3Department of Urology and Urological Oncology, Multidisciplinary Hospital in Lublin, Lublin, Poland; 4l Department of Surgical Oncology, St. John’s Cancer Center, Lublin, Poland; 5Department of Normal, Clinical and Imaging Anatomy, Medical University of Lublin, Lublin, Poland*These authors contributed equally to this workCorrespondence: Monika Szewc, Department of Normal, Clinical and Imaging Anatomy, Medical University of Lublin, Lublin, 20-950, Poland, Email m.szewc456@gmail.comPurpose: The study of the cytotoxic effect of variously substituted indole- and benzimidazo[1,2-c]quinazolines may prove particularly valuable in the context of developing new, effective anticancer therapies based on MSCs. The unique ability of MSCs to migrate and inhabit the tumor microenvironment makes them an ideal tool for transferring chemotherapeutic agents. The aim of this study was to evaluate the cytotoxic activity of 4-(6-indolo[1,2-c]quinazoline)2-methyl-benzene-1,3-diol (compound A) and 4-(6-benzimidazolo[1,2-c]quinazoline)2-methyl-benzene-1,3-diol (compound B) relative to the adipose-derived mesenchymal stem cells line (ASC52-telo) and the fibroblast line (HDFa).Materials and Methods: The test was performed on commercial cell lines: ASC52-telo and HDFa which were incubated with compounds A and B at four concentrations: 1 μg/mL, 2 μg/mL, 4 μg/mL, 8 μg/mL for 48 and 72 hours. The MTT test was performed to assess the cytotoxicity and determine the IC50 value of compounds A and B against both tested cell lines.Results: The results of the research indicate that both tested compounds showed stronger cytotoxic activity towards ASC52-telo than HDFa cells. In addition, compound A is characterized by greater cytotoxicity towards both tested cell lines compared to compound B.Conclusion: The indole- and benzimidazo[1,2-c]quinazolines used in the study could potentially be used in MSCs-based therapy. There is a need to further investigate the safety of using MSCs as drug carriers, and to examine the anticancer activity of the tested compounds, as well as to perform additional and valuable assays, such as enzymatic and toxicity tests.Keywords: substituted quinazoline derivatives, stem cells therapy, MSC-based cell therapy, anticancerstrategy